Design of CNC Device Designed for Automation of the Application of Viscous Materials - Drgona, Peter; Stefun, Rastislav; Stefke, Lubomir (Communications - Scientific Letters of the University of Zilina, 2018)
This article deals with the design and practical realization of a CNC device designed for the application of viscous materials, such as a thermal conducting paste. Nowadays, growing trend of usage of electronic circuits in transportation systems is observed. Switched mode power supplies are widely used in all types of means of transport and their infrastructure. For correct operation of power converters, produced heat must be dissipated. Thermal conducting paste is used for better heat dissipating but its application on surface can be an issue. Designed CNC device serves for easier and more accurate application in production process in transport industry.
Keywords: automation in transportation system; CNC design; CNC control; ball screw; stepper motor